2020
DOI: 10.1101/2020.05.07.083220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Demonstration of Patient-Specific Simulations To Assess Left Atrial Appendage Thrombogenesis Risk

Abstract: Atrial fibrillation (AF) alters left atrial (LA) hemodynamics, which can lead to thrombosis in the left atrial appendage (LAA), systemic embolism and stroke. A personalized risk-stratification of AF patients for stroke would permit improved balancing of preventive anticoagulation therapies against bleeding risk. We investigated how LA anatomy and function impact LA and LAA hemodynamics, and explored whether patient-specific analysis by computational fluid dynamics (CFD) can predict the risk of LAA thrombosis. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…By employing rigid RA walls, and having into account the mass conservation balance, all flow entering this chamber must be equal to the flow exiting the TV, which is not physiologically accurate. Moreover, fixed-wall simulations oversimplify inflow-outflow boundary conditions and ignore atrial-ventricular interactions; they have been shown to yield different flow fields and stasis maps [ 71 ] and overestimate instantaneous quantities (e.g. flow velocity; WSS) when compared to moving wall simulations [ 72 ]; however, time-averaged quantities have been shown not to greatly vary [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…By employing rigid RA walls, and having into account the mass conservation balance, all flow entering this chamber must be equal to the flow exiting the TV, which is not physiologically accurate. Moreover, fixed-wall simulations oversimplify inflow-outflow boundary conditions and ignore atrial-ventricular interactions; they have been shown to yield different flow fields and stasis maps [ 71 ] and overestimate instantaneous quantities (e.g. flow velocity; WSS) when compared to moving wall simulations [ 72 ]; however, time-averaged quantities have been shown not to greatly vary [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding to the blood flow velocity, the time when the blood stays in the LAA and blood flow energy-related indicators are also ideal tools. If the average residence time in LAA is more than 2 s, a thrombus can be formed (54). These parameters all have the potential to be used in clinical practice; for example, the high sensitivity of LAD (96.7%) exhibits its potential to be used for the accurate prediction of patients' relatively high risk when doctors are in doubt.…”
Section: Hemodynamic Indexes and Their Predictive Value For Thrombosi...mentioning
confidence: 99%
“…Studies have shown that fixed wall simulation can be reflect the flow patterns of LA and LAA well in dysfunctional atrium. In sinus rhythm, the risk of thrombosis can still be assessed, although with some limitations (38). Therefore, the heart wall in this paper was set up as a rigid noslip wall.…”
Section: Solving Processmentioning
confidence: 99%